2013
DOI: 10.5424/sjar/2013112-3558
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of soil carbon sink by cover crops in olive orchards under semiarid conditions. Influence of the type of soil and weed

Abstract: The olive tree is one of the most important crops in Spain, and the main one in the region of Andalusia. Most orchards are rain-fed, with high slopes where conventional tillage (CT) is the primary soil management system used. These conditions lead to high erosion and a significant transport of organic carbon (OC). Moreover, soil tillage accelerates the oxidation of the OC. Cover crops (CC) are the conservation agriculture (CA) approach for woody crops. They are grown in-between tree rows to protect the soil ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 44 publications
0
24
1
1
Order By: Relevance
“…Some authors indicate that tillage could decrease soil organic matter by between 30% and 50% in a few years (Robert et al, ), and that losses could reach 60% (Jones, Yli‐Halla, Demetriades, Leifeld, & Robert, ). In our trials, the SOC loss was decreased by over 90% with the use of cover crops, slightly higher results than those of Márquez‐García, González‐Sánchez, Castro‐García, and Ordóñez‐Fernández (), who obtained a reduction of 80.5% of soil loss and 67.7% of SOC loss, in 4 years. The reductions in this study agree with those obtained by Gómez, Guzmán, et al (), who used a cover crop of Lolium in a 4‐year experiment carried out in bigger plots and on an 11% slope under natural rainfall.…”
Section: Resultscontrasting
confidence: 59%
“…Some authors indicate that tillage could decrease soil organic matter by between 30% and 50% in a few years (Robert et al, ), and that losses could reach 60% (Jones, Yli‐Halla, Demetriades, Leifeld, & Robert, ). In our trials, the SOC loss was decreased by over 90% with the use of cover crops, slightly higher results than those of Márquez‐García, González‐Sánchez, Castro‐García, and Ordóñez‐Fernández (), who obtained a reduction of 80.5% of soil loss and 67.7% of SOC loss, in 4 years. The reductions in this study agree with those obtained by Gómez, Guzmán, et al (), who used a cover crop of Lolium in a 4‐year experiment carried out in bigger plots and on an 11% slope under natural rainfall.…”
Section: Resultscontrasting
confidence: 59%
“…The characteristics of the Mediterranean type of climate, where long dry periods alternate with intense rainfall events, in conjunction with soil management systems that pursue bare soils to minimize water competition by weeds entail a high susceptibility to severe water erosion of the soil (Gómez et al, 2014a). Therefore, the use of cover crops has been promoted for soil protection, given their proven effectiveness in controlling water erosion (Gómez et al, 2004(Gómez et al, , 2009aMárquez-García et al, 2013;Taguas et al, 2013, among others). In fact, growing crops in between the olive tree rows is currently a compulsory requirement if the mean slope of the plot is over 15 %, according to cross-compliance rules (European Commission, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…cellulose) in the soil, which consequently induced a loss of soil carbon. Several previous studies have shown that tillage in olive orchards induced the loss of soil organic carbon because of the large rate of mineralization that results from the break‐up of soil aggregates; this is a serious threat under Mediterranean conditions (Gómez et al ., ; Vanwalleghem et al ., ; Marquez‐Garcia et al ., ). Moreover, we found that lipase activity was greater in non‐tilled soil than after tillage in the coastal area (Figure b).…”
Section: Resultsmentioning
confidence: 97%